Weakening of carbon sink on the Qinghai–Tibet Plateau - Tonghua Wu; Wensi Ma; Xiaodong Wu (Zenodo, 2022)
The file " Code for improved IBIS model.rar "is the improved IBIS model code applied for the paper "Weakening of carbon sink on the Qinghai–Tibet Plateau" whichhave been published in Geoderma. The data files include all data the paper applied in the context.